Spatiotemporal dynamics of NF-κB/Dorsal inhibitor IκBα/Cactus in Drosophila blastoderm embryos - Allison E. Schloop; Sharva Vijayakumar Hiremath; Razeen Shaikh; Sadia Siddika Dima; Leslie Lizardo; Amrit Bhakta; Cranos M. Williams; Gregory T. Reeves (iScience)
Summary: The NF-κB/IκBα pathway regulates key cellular processes, including development, immunity, and inflammation. In Drosophila, the homologous Dorsal/Cactus system patterns the dorsoventral axis of the blastoderm embryo. While the inhibitor Cactus has been suggested to play multiple roles in regulating Dorsal, direct visualization of Cactus is challenging due to its rapid turnover. To overcome this challenge, we endogenously tagged Cactus with a nanobody against GFP and quantitatively imaged Cactus distribution in live embryos. We found that, like Dorsal, Cactus undergoes nuclear-cycle driven dynamics and nucleocytoplasmic shuttling. Using a mathematical model constrained by our data, we estimated Cactus nuclear and cytoplasmic concentration. Our results imply that the Dorsal gradient has increased spatial range, robustness, and precision due to the presence of Cactus in the nucleus uniformly throughout the embryo. This study provides insights into NF-κB regulation in Drosophila embryos and highlights the need for similar quantitative studies in other biological systems.